MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN PRODUKTIVITAS PEKERJA HARIAN LEPAS DI TENGAH KETIDAKPASTIAN EKONOMI DI KOTA TANGERANG - Surahman, Hendy (Yayasan Education and Social Center, 2025)
This study aims to analyze the factors influencing the productivity of daily workers in Tangerang City, focusing on the role of human resource management amidst economic uncertainty. The results reveal that economic uncertainty significantly affects workers' motivation and performance, leading to reduced productivity. Fluctuating incomes and job instability contribute to worker anxiety and a lack of enthusiasm in their tasks. Furthermore, inefficient human resource management, particularly in training and fair incentive distribution, hinders productivity. Despite some employers offering performance-based incentives, the system is not applied evenly, limiting its benefits for workers. The study also highlights the importance of skills development, as workers with higher skills tend to be more productive. In conclusion, the study emphasizes the need for effective human resource management to boost the productivity of daily workers, especially in uncertain economic conditions like those in Tangerang City.